2019
DOI: 10.1097/pr9.0000000000000754
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of patients' presurgery perceptions of surgeon attributes to the experience of trust and pain during third molar surgery

Abstract: Background:Patients' feeling of trust in their surgeon may modulate the experience of pain during surgery. However, factors that contribute to patients' experience of trust during surgery remain underexamined. The current study examined the contribution of patients' impressions of surgeons' warmth and competence to their experience of trust and pain during wisdom tooth extractions.Methods:Patients (N = 135, 47% female) scheduled for a wisdom tooth extraction reported their current distress and impressions of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…The present results are the first to indicate that written pre-consultation information about physicians' skills, which is increasingly available and consulted online, does not only affect patients' selection of a physician [1,4], but also patients' pre-consultation trust and treatment outcome expectancies. Trust and outcome expectancies in turn are known to impact the patient-physician relationship [5,6] and treatment adherence and outcomes [10,11,[13][14][15][16] and are considered core mechanisms of placebo effects [24]. Notably, the observed effect sizes preliminary indicate that views of physicians' competence affect expected treatment outcomes more strongly than views of empathic skills, although these differences were not observed in previous research where competence and empathy were manipulated in the lab [12].…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The present results are the first to indicate that written pre-consultation information about physicians' skills, which is increasingly available and consulted online, does not only affect patients' selection of a physician [1,4], but also patients' pre-consultation trust and treatment outcome expectancies. Trust and outcome expectancies in turn are known to impact the patient-physician relationship [5,6] and treatment adherence and outcomes [10,11,[13][14][15][16] and are considered core mechanisms of placebo effects [24]. Notably, the observed effect sizes preliminary indicate that views of physicians' competence affect expected treatment outcomes more strongly than views of empathic skills, although these differences were not observed in previous research where competence and empathy were manipulated in the lab [12].…”
Section: Discussionmentioning
confidence: 80%
“…While previous research found that such online information may influence patients' choice of physician [1,4], it is largely unknown how such information may affect patients' trust in physicians and treatment outcome expectancies, which are important predictors of treatment outcomes. Particularly the communication of physicians' competence and empathic skills may impact whether patients experience their physician as trustworthy [5,6]. Trust in one's physician is highly important for patient wellbeing, and likely especially when patients are confronted with a potentially life-threatening illness such as cancer, when a sense of vulnerability is high [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…In this line, a study published by Ashton-James et al . ( 33 ) determines experience in terms of the number of 3M extractions performed throughout the professional career. Although few, some studies have linked the surgeon's experience with post-operative complications and morbidity and have found more complications in less experienced professionals ( 34 , 35 ) or non-specialized generalists ( 35 , 36 ), as well as greater post-operative morbidity when the procedure is performed by generalists ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…This theme issue covers both theoretical and original research articles exploring how often overlooked aspects of patient's medical encounters and experiences can influence health outcomes through the placebo and nocebo effects in pain medicine. Namely, the 5 articles and 3 reviews included in this special issue illustrate how a variety of factors, ranging from perception of competence and warmth before a surgical procedure 1 to psychological changes occurring as a result of treatment framing, 9 alter pain experience and placebo effects. Other factors discussed include the role of expectations, desire for pain relief, and anxiety in pain-relieving intervention such as medial branch radiofrequency neurotomy low back pain patients, 8 an online method of placebo manipulation, 17 and operant conditioning with avoidance movements.…”
mentioning
confidence: 99%
“…Patients' feelings of surgeons' warmth and competence assessed immediately before wisdom tooth extraction surgery influenced the patients' postsurgical experiences of trust and acute pain; when patients perceived the surgeon as highly competent, but not warm, they experienced higher trust and lower pain during surgery. 1 Thus, a key aspect of the patient–clinician interactions is competence of health practitioners while interacting with their patients and the impression they create.…”
mentioning
confidence: 99%